The digital and AI coaches' handbook : the complete guide to the use of online, AI and technology in coaching - Passmore, Jonathan; Diller, Sandra J.; Isaacson, Sam; Brantl, Maximilian (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This comprehensive practitioner guide supports coaches in developing their understanding of digital technologies and how to work in digital environments. Many coaches are looking to better understand how to work in these ever-changing environments and to craft their own coaching practices to take advantage of working online, and this book shows us how. The practice of coaching has undergone significant change, with technology widely embedded and used in professional coaching services today. Coaching practitioners worldwide are adapting to digital environments and a host of new technological tools have come into play, from the developments in virtual reality to AI-informed coaching, and from coaching bots to workplace apps. Edited by Jonathan Passmore, Sandra Diller, Sam Isaacson and Maximilian Brantl, this third book in the acclaimed Coaches' Handbook series brings together internationally respected coaching experts and practitioners to share the most up-to-date know-how. The book takes you through key technical developments, the critical factors in making digital coaching successful and how to build a coaching business using these technologies. The book also considers the impacts on the wider industry and concludes with a number of case studies of global coaching organisations and their experiences of using digital techniques, including CoachHub, BetterUp and EZRA. Aimed at coach practitioners, their supervisors, trainers, and student coaches on accreditation programmes or undertaking training for a certificate in coaching, this book showcases best practice, new ideas and the science behind the digital revolution within coaching practice and the coaching industry"--
Keywords: Personal coaching -- Technological innovations; Artificial intelligence; BUSINESS & ECONOMICS / Human Resources & Personnel Management